Tidal flats' faunal resource utilization in Catanduanes Island, Philippines: gleaning, fishing, and their associated provisioning and cultural services - Aldea, Kristian Q.; Tumala, Zyra Mae T. (Frontiers in Sustainability, 2025)
Tidal flats are identified as a food-rich coastal zone, yet despite this recognition, information on food provisioning and its associated cultural services remains relatively understudied. To address these gaps, we first investigated the tidal flat species caught and their metrics (time spent, catch quantities, frequency of utilization, income), and second, explored the cultural benefits of gleaning and fishing through an explanatory sequential mixed-method design. The data were gathered through surveys, individual interviews, and focused-group discussions with the gleaners and fishers, the two main livelihood groups in the tidal flats. Our results suggest that tidal flats provide diverse species, reflecting utilization types and various gleaning/fishing methods, which generate food and income for coastal communities. Considering the current utilization schemes, it is inferred that the activities are sustainable, although assessments may be necessary to develop an informed policy framework while maintaining their livelihood value. Various cultural services evolved from the utilization linked to wellbeing, which includes the following: social cohesion and knowledge transfer, sense of place and connection, recreation and leisure, stress relief and social repair, and children's natural discovery learning. Personal and shared experiences associated with the tidal flats may thrive through narratives and intergenerational practices, potentially contributing to the preservation of cultural heritage in the coastal environments. Integrating the tidal flats' conservation is hereby recommended for coastal resource management in the island.